2021
DOI: 10.3390/rs13101949
|View full text |Cite
|
Sign up to set email alerts
|

Local- and Regional-Scale Forcing of Glacier Mass Balance Changes in the Swiss Alps

Abstract: Glacier mass variations are climate indicators. Therefore, it is essential to examine both winter and summer mass balance variability over a long period of time to address climate-related ice mass fluctuations. In this study we analyze glacier mass balance components and hypsometric characteristics with respect to their interactions with local meteorological variables and remote large-scale atmospheric and oceanic patterns. The results show that all selected glaciers have lost their equilibrium condition in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…These are categorized as following: i, The old stage if HI≤0.35, in which the basin is fully stabilized; ii, the complete stage is 0.35≤ HI ≤0.60, which means the basin growth has attained a steady-state disorder and iii, in the early stage if HI ≥0.60, where the basin is highly liable to erosion and is under expansion (Shivaswamy, et al, 2019). As shown in Table (2) the values of HI, for sub-basins in the study area varied between 0.37 and 0.57 indicating that 34 sub-basins in the study area belong to the mature stage of moderated erosion, not affected by tectonic or geological disturbance (Gharehchahi et al, 2021).…”
Section: Hypsometric Integral (Hi)mentioning
confidence: 87%
“…These are categorized as following: i, The old stage if HI≤0.35, in which the basin is fully stabilized; ii, the complete stage is 0.35≤ HI ≤0.60, which means the basin growth has attained a steady-state disorder and iii, in the early stage if HI ≥0.60, where the basin is highly liable to erosion and is under expansion (Shivaswamy, et al, 2019). As shown in Table (2) the values of HI, for sub-basins in the study area varied between 0.37 and 0.57 indicating that 34 sub-basins in the study area belong to the mature stage of moderated erosion, not affected by tectonic or geological disturbance (Gharehchahi et al, 2021).…”
Section: Hypsometric Integral (Hi)mentioning
confidence: 87%
“…A hypsometric integral (HI) is a macroscopic indicator that can be used to study the quantitative relationship between the area of a regional horizontal section of an area and its elevation, which can reflect the state of watershed development (Chen et al, 2003;Hamdouni et al, 2008;Andreani et al, 2014;Qing et al, 2020;Gharehchahi et al, 2021). The origin of HIs can be traced back to Darwin's theory of evolution (Slaymaker, 1972;Kowall, 1976), which was applied to characterize the surface of the Earth in the late 19th century (Bannister, 1980;Lifton and Chase, 1992;Hiroo, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the findings of several other studies for the region, the authors reported that the glacier centerline velocity showed slight increase during 2017-2020. Glacier mass balance estimations are one of the most reliable parameters used to examine the health of a glacier, and Gharehchahi et al [7] performed a regional-scale analysis to understand the impact of local and regional climate forcing on the glacier mass balance changes in the Swiss Alps. The results indicated the loss of equilibrium condition in recent decades for all the studied glaciers, with negative mass balance trends and decreasing accumulation areas, as a result of increasing air temperatures of ≥+0.45 • C decade −1 .…”
mentioning
confidence: 99%
“…The results indicated the loss of equilibrium condition in recent decades for all the studied glaciers, with negative mass balance trends and decreasing accumulation areas, as a result of increasing air temperatures of ≥+0.45 • C decade −1 . Gharehchahi et al [7] also reported considerable controls of the Atlantic multidecadal oscillation (AMO), Greenland blocking index (GBI), and East Atlantic (EA) teleconnections on the interannual variability of summer and winter mass balances. The authors [7] further corroborated their findings with the analysis of decadal frontal retreat using Landsat images from 1984 to 2014.…”
mentioning
confidence: 99%
See 1 more Smart Citation